Project Based Learning Digital untuk Pembelajaran Buku Fiksi dan Nonfiksi di Kelas VII - Rahmadi, Rahmadi (Jurnal Pendidikan Dirgantara, 2025)
The rapid development of digital technology demands that literature learning in junior secondary schools be delivered in a more interactive and student–relevant manner. However, classroom practices remain dominated by lecture-based instruction, resulting in low student engagement and limited appreciation of literary texts. This study aims to describe the use of digital media in teaching fiction and nonfiction texts in Grade VII, as well as to explore students’ experiences and challenges during project based learning activities. Employing a qualitative descriptive design, the study involved Grade VII students and a Bahasa Indonesia teacher. Data were collected through classroom observations, in-depth interviews, and documentation of students’ digital project outputs. Data were analyzed through reduction, display, and conclusion drawing. The findings indicate that integrating digital media with Project Based Learning enhances student engagement through text analysis, group discussions, and digital project creation. Learning also becomes more inclusive through ability-based grouping and more meaningful when materials are connected to students’ local cultural contexts. The study concludes that digital media combined with PBL strengthens students’ literary literacy and learning motivation. The implications suggest that teachers need to develop stronger digital pedagogical competencies and schools should provide adequate technological support.